(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The study aimed to identify the population disparity gap in Libya, which the researcher perceived as hindering the implementation of sustainable development in the country. This led us to attempt to answer the main question of the study: Does addressing spatial disparity geographically play an active role in achieving sustainable development in Libya? In line with the overall objective of the study, which is to identify the types of natural resources in Libya to determine effective methods and their utilization for achieving sustainable development, the researcher employed an analytical and deductive approach to extract the study’s results. Among the most important findings were the necessity of preserving stable and growing population density throughout Libya, dismantling the centralization that hinders the just implementation of development projects, ensuring human security and appropriate economic growth to achieve sustainable development. Furthermore, it highlighted the need to address the lack of a stable political climate and the absence of scientific administration, which negatively impacted the utilization of the nation’s valuable resources, lowered the per capita income of Libyans, increased the prices of goods in their livelihoods, and the failure to provide genuine plans for implementing equitable and proper spatial development. This has halted sustainable development plans in the present and for future generations in these years. Moreover, exacerbating the problem is the concentration of human development in the cities of northern Libya, specifically in major cities, which has had a negative impact on neglecting towns and villages in the central, eastern, and southern regions. Additionally, equitable spatial development achieves the advantage of increasing individuals’ sense of belonging to their homeland, eliminating cases of alienation and internal or external migration. As sustainable development has become a strategic choice for the well-being of future generations, it takes on various forms.